1996
DOI: 10.1111/j.1528-1157.1996.tb00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Tooth‐Brushing Epilepsy: A Report of a Case with Structural and Functional Imaging and Electrophysiology Demonstrating a Right Frontal Focus

Abstract: Patients with reflex epilepsies may provide insights into cerebral pathophysiology. We report a patient with an unusual form of reflex epilepsy in whom seizures are induced by tooth brushing. Magnetic resonance imaging (MRI) demonstrated a right posterior frontal low-grade tumor predominantly involving the precentral gyrus. Video-telemetry demonstrated right-sided epileptiform activity during a typical induced complex partial seizure. An ictal single photon emission computed tomography (SPECT) scan showed an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 12 publications
2
27
1
Order By: Relevance
“…Epilepsy associated with toothbrushing is an unusual form of reflex epilepsy in which seizures are precipitated exclusively by the act of brushing the teeth [53][54][55][56]. Such epilepsy involves a persistent rhythmic oral sensory stimulus, which is likely to evoke the neuronal synchronization necessary to induce seizures [57].…”
Section: Discussionmentioning
confidence: 98%
“…Epilepsy associated with toothbrushing is an unusual form of reflex epilepsy in which seizures are precipitated exclusively by the act of brushing the teeth [53][54][55][56]. Such epilepsy involves a persistent rhythmic oral sensory stimulus, which is likely to evoke the neuronal synchronization necessary to induce seizures [57].…”
Section: Discussionmentioning
confidence: 98%
“…O’Brien and his colleagues proposed that lesions in those patients interfered with the inhibition or processing of sensory inputs to the cortex and, consequently, led to excitation and production of a critical mass of synchronised cortical neurons 4. Although traditionally controversial, seizures of subcortical and infratentorial origin have been demonstrated in animal models and are well documented in patients with hypothalamic hamartomas and cerebellar dysplastic lesions 5 6.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, O' Brien et al (2) reported a 23‐year‐old woman who had (for the last 10–12 years) partial seizures consisting of tonic posturing of the left arm, head and eye deviation to the left, and left hemifacial jerking. Her seizures were triggered exclusively by vigorous tooth brushing on either side of mouth and were relatively resistant to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Reflex epileptic seizures triggered by tooth brushing are rare but well documented. Holmes et al (1982) were the first to describe a patient with seizures consistently but not exclusively provoked by tooth brushing (1), and O'Brien et al (2) reported another patient with a clearly symptomatic form of this condition. We report a woman with late‐onset seizures occurring exclusively during tooth brushing, which were not associated with any apparent brain lesion, and responded readily to single‐drug treatment.…”
mentioning
confidence: 99%